Detection of several carbapenems resistant and virulence genes in classical and hyper-virulent strains of Klebsiella pneumoniae isolated from hospitalized neonates and adults in Khartoum - Aalaa Mahgoub Albasha; Esraa hassan Osman; Saga Abd-Alhalim; Elianz F. Alshaib; Leena Al-Hassan; Hisham N. Altayb (BMC Research Notes, 2020)
Abstract Objective Klebsiella pneumoniae (K. pneumoniae) involves both community-acquired and nosocomial infections. It is responsible for a wide variety of infections, including infections of the urinary tract, pneumonia, bacteremia, meningitis, wound infection and purulent abscesses. We constructed this study to detect several carbapenems resistant and virulence genes in classical and hyper-virulent strains of K. pneumoniae isolated from hospitalized neonates and adults in Khartoum state. Results Seventy percent of the isolates were resistant to ceftazidime, 18(30%) to ciprofloxacin, 23(38.3%) to chloramphenicol, 24(40%) to gentamicin and 8% to imipenem, 35% were multidrug-resistant, and 7% extensively drug-resistant, all blood isolates (n = 14) were resistant to ceftazidime. entB was the most predominant virulence gene (93.3%), followed by mrkD (78.3%), kfu (60%), K2 (51.7%), magA (18.3%) and rmpA (5%). bla OXA-48 was the most predominant carbapenem-resistant gene (68.3%), followed by bla NDM (10%), bla KPC (8.3%), and bla IMP (3.3%). Eight hyper-virulent strains were positive for bla OXA-48 and two for bla NDM genes.